High-strength magnetic shoe and production process thereof
By adjusting the raw material ratio of the permanent magnet ferrite magnet tiles and adopting a specific production process, the problem of insufficient mechanical strength of the magnet tiles is solved, the strength and toughness of the magnet tiles are improved, and the service life of the motor is extended.
Patent Information
- Application Number
- CN202411447650.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
AI Technical Summary
The mechanical strength of permanent magnet ferrite tiles is insufficient, resulting in easy breakage or fracture during grinding or use, shortening the service life of the motor.
By adjusting the raw material ratio, adding zirconia and yttrium oxide, and adopting process steps such as ball milling, molding, pre-sintering, rough grinding, fine grinding, wet pressing molding and sintering, high-strength magnetic tiles are prepared.
The mechanical strength and fracture toughness of magnetic tiles are increased, the density is increased, and the service life of the motor is prolonged.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic tile production, and in particular relates to a high-strength magnetic tile and a production process thereof. Background Art
[0002] Permanent ferrite is a hexagonal compound with uniaxial anisotropy, mainly barium, strontium, lead and their composite solid solutions. Since this type of ferrite material can still retain strong constant residual magnetic properties for a long time after the external magnetizing field disappears, it can be used to generate a constant magnetic field in the external space. Permanent ferrite tiles are widely used in terminal consumer products such as automobiles, home appliances, consumer electronics, computers, and communication products, and are an important component of these products - the motor.
[0003] The quality of permanent ferrite magnetic tiles is not only reflected in the magnetic properties, dimensional tolerances, and appearance that meet national standards and user requirements, but also an important quality characteristic parameter is mechanical strength. If the mechanical strength of the tiles does not meet the requirements, they are prone to breakage or fracture during grinding or magnetization after grinding, or they may break during use after installation, which significantly shortens the service life and causes the motor rotor to get stuck and stop, resulting in the motor being scrapped. Since tiles with poor mechanical strength have normal appearance and no obvious cracks can be seen, it is difficult to detect them in time before use, which inevitably causes failures during use. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength magnetic tile and a production process thereof, so as to improve the mechanical strength of the permanent ferrite magnetic tile.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] The present invention provides a high-strength magnetic tile, which comprises the following raw materials in parts by weight:
[0007] 80-90 parts of ferric oxide, 12-15 parts of strontium carbonate, 0.4-0.6 parts of calcium carbonate, 0.1-0.2 parts of zirconium oxide, 0.5-0.7 parts of boric acid, 0.5-0.7 parts of cobalt oxide, 2-6 parts of yttrium oxide, 0.3-0.5 parts of silicon dioxide and 0.2-0.4 parts of bismuth oxide.
[0008] The present invention also provides a production process of a high-strength magnetic tile, comprising the following steps:
[0009] S1. Use a ball mill to mill the raw materials according to the proportion to obtain a primary slurry;
[0010] S2, the primary slurry is screened and then prepared into balls by a molding machine, and the balls are pre-sintered in a push-plate kiln to obtain pre-sintered materials;
[0011] S3, crushing the completely reacted pre-burned material, and then performing coarse grinding and fine grinding in sequence, and then screening and secondary ball milling to obtain secondary slurry;
[0012] S4, filtering the secondary slurry and wet pressing it to obtain a green body;
[0013] S5. Sintering the green body in a push plate kiln, and performing surface treatment after cooling to obtain magnetic tiles.
[0014] Furthermore, the ball milling time in S1 is 2-3 hours, and the particle size of the primary slurry is 0.1-2.0 μm.
[0015] Furthermore, the material ball is a honeycomb sphere with a through hole in the middle and a diameter of 100 mm.
[0016] Furthermore, the pre-sintering temperature in S2 is 1150-1280° C., and the pre-sintering holding time is 2-3 hours.
[0017] Furthermore, the oxygen content in the push plate kiln in S2 is 9-10%.
[0018] Furthermore, the pre-burned material in S3 is crushed by a jaw crusher, the crushed pre-burned material is coarsely ground by a vibration mill, and the coarsely ground pre-burned material is finely ground by a planetary ball mill.
[0019] Furthermore, the particle size of the secondary slurry is 0.6-0.7 μm.
[0020] Furthermore, the magnetic field of the wet pressing molding is 800-1000KA / m.
[0021] Furthermore, the sintering temperature is 1260-1290° C., and the sintering holding time is 1-2 hours.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention adds zirconium oxide to the raw materials before pre-sintering. On the one hand, it can be precipitated on the grain boundaries of ferrite during the pre-sintering process, making the particle size distribution of the secondary slurry narrower and the particle size smaller, thereby increasing the density of the finished product and the mechanical strength. On the other hand, the tetragonal zirconium oxide is transformed into the monoclinic zirconium oxide, which has a phase change toughening effect, can improve the fracture toughness of the magnetic tile, and increase the strength.
[0024] (2) The present invention adds yttrium oxide to the raw material, and the rare earth element yttrium is doped to replace Fe 3+ , which can increase the remanence and intrinsic coercive force of the magnetic tile, and yttrium oxide has the effect of stabilizing the tetragonal crystal of zirconia, which can make the magnetic tile have the maximum phase change toughening effect under the action of external stress and improve the strength of the magnetic tile. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] The high-strength magnetic tile in this embodiment includes the following raw materials by weight:
[0028] 80 parts of ferric oxide, 12 parts of strontium carbonate, 0.4 parts of calcium carbonate, 0.1 parts of zirconium oxide, 0.5 parts of boric acid, 0.5 parts of cobalt oxide, 2 parts of yttrium oxide, 0.3 parts of silicon dioxide and 0.2 parts of bismuth oxide.
[0029] S1. Use a ball mill to mill the raw materials according to the ratio for 2 hours to obtain a slurry. The particle size of the slurry is 0.1-2.0 μm.
[0030] S2, the primary slurry is sieved and then prepared into a honeycomb spherical ball with a through hole in the middle by a molding machine, the ball diameter is 100 mm, the ball enters the push plate kiln for pre-sintering, the pre-sintering temperature is set to 1280 ° C, the heat preservation time is 2h, the oxygen content of the push plate kiln is 9%, and the pre-sintered material is obtained after the pre-sintering is completed;
[0031] S3, the pre-burned material after the reaction is completely screened and impurities are removed, and then crushed by a jaw crusher, and then put into a vibration mill for coarse grinding, and after coarse grinding, it is screened and put into a planetary ball mill for secondary ball milling to obtain a secondary slurry, and the particle size of the secondary slurry is 0.6-0.7μm;
[0032] S4, filtering the secondary slurry and wet pressing the slurry under a magnetic field with a magnetic field strength of 800KA / m to obtain a green body;
[0033] S5. Sinter the green body in a push plate kiln, set the sintering temperature to 1260°C, keep warm for 2 hours, and perform surface treatment after cooling to obtain magnetic tiles.
[0034] Example 2
[0035] The high-strength magnetic tile in this embodiment includes the following raw materials by weight:
[0036] 80 parts of ferric oxide, 12 parts of strontium carbonate, 0.4 parts of calcium carbonate, 0.15 parts of zirconium oxide, 0.5 parts of boric acid, 0.5 parts of cobalt oxide, 3.75 parts of yttrium oxide, 0.3 parts of silicon dioxide and 0.2 parts of bismuth oxide.
[0037] S1. Use a ball mill to mill the raw materials according to the ratio for 2 hours to obtain a slurry. The particle size of the slurry is 0.1-2.0 μm.
[0038] S2, the primary slurry is sieved and then prepared into a honeycomb spherical ball with a through hole in the middle by a molding machine, the ball diameter is 100 mm, the ball enters the push plate kiln for pre-sintering, the pre-sintering temperature is set to 1280 ° C, the heat preservation time is 2h, the oxygen content of the push plate kiln is 9%, and the pre-sintered material is obtained after the pre-sintering is completed;
[0039] S3, the pre-burned material after the reaction is completely screened and impurities are removed, and then crushed by a jaw crusher, and then put into a vibration mill for coarse grinding, and after coarse grinding, it is screened and put into a planetary ball mill for secondary ball milling to obtain a secondary slurry, and the particle size of the secondary slurry is 0.6-0.7μm;
[0040] S4, filtering the secondary slurry and wet pressing the slurry under a magnetic field with a magnetic field strength of 800KA / m to obtain a green body;
[0041] S5. Sinter the green body in a push plate kiln, set the sintering temperature to 1260°C, keep warm for 2 hours, and perform surface treatment after cooling to obtain magnetic tiles.
[0042] Example 3
[0043] The high-strength magnetic tile in this embodiment includes the following raw materials by weight:
[0044] 80 parts of ferric oxide, 12 parts of strontium carbonate, 0.4 parts of calcium carbonate, 0.2 parts of zirconium oxide, 0.5 parts of boric acid, 0.5 parts of cobalt oxide, 6 parts of yttrium oxide, 0.3 parts of silicon dioxide and 0.2 parts of bismuth oxide.
[0045] S1. Use a ball mill to mill the raw materials according to the ratio for 2 hours to obtain a slurry. The particle size of the slurry is 0.1-2.0 μm.
[0046] S2, the primary slurry is sieved and then prepared into a honeycomb spherical ball with a through hole in the middle by a molding machine, the ball diameter is 100 mm, the ball enters the push plate kiln for pre-sintering, the pre-sintering temperature is set to 1280 ° C, the heat preservation time is 2h, the oxygen content of the push plate kiln is 9%, and the pre-sintered material is obtained after the pre-sintering is completed;
[0047] S3, the pre-burned material after the reaction is completely screened and impurities are removed, and then crushed by a jaw crusher, and then put into a vibration mill for coarse grinding, and after coarse grinding, it is screened and put into a planetary ball mill for secondary ball milling to obtain a secondary slurry, and the particle size of the secondary slurry is 0.6-0.7μm;
[0048] S4, filtering the secondary slurry and wet pressing the slurry under a magnetic field with a magnetic field strength of 800KA / m to obtain a green body;
[0049] S5. Sinter the green body in a push plate kiln, set the sintering temperature to 1260°C, keep warm for 2 hours, and perform surface treatment after cooling to obtain magnetic tiles.
[0050] Example 4
[0051] The high-strength magnetic tile in this embodiment includes the following raw materials by weight:
[0052] 85 parts of ferric oxide, 14 parts of strontium carbonate, 0.5 parts of calcium carbonate, 0.15 parts of zirconium oxide, 0.6 parts of boric acid, 0.6 parts of cobalt oxide, 3.75 parts of yttrium oxide, 0.4 parts of silicon dioxide and 0.3 parts of bismuth oxide.
[0053] S1. Use a ball mill to mill the raw materials according to the ratio for 2.5 hours to obtain a slurry. The particle size of the slurry is 0.1-2.0 μm.
[0054] S2, the primary slurry is sieved and then prepared into a honeycomb spherical ball with a through hole in the middle by a molding machine, the ball diameter is 100 mm, the ball enters the push plate kiln for pre-sintering, the pre-sintering temperature is set to 1190 ° C, the heat preservation time is 2.5h, the oxygen content of the push plate kiln is 9.6%, and the pre-sintered material is obtained after the pre-sintering is completed;
[0055] S3, the pre-burned material after the reaction is completely screened and impurities are removed, and then crushed by a jaw crusher, and then put into a vibration mill for coarse grinding, and after coarse grinding, it is screened and put into a planetary ball mill for secondary ball milling to obtain a secondary slurry, and the particle size of the secondary slurry is 0.6-0.7μm;
[0056] S4, filtering the secondary slurry and wet pressing the slurry under a magnetic field with a magnetic field strength of 950KA / m to obtain a green body;
[0057] S5. Sinter the green body in a push plate kiln, set the sintering temperature to 1280°C, keep the temperature for 1.5h, and perform surface treatment after cooling to obtain magnetic tiles.
[0058] Example 5
[0059] The high-strength magnetic tile in this embodiment includes the following raw materials by weight:
[0060] 90 parts of ferric oxide, 15 parts of strontium carbonate, 0.6 parts of calcium carbonate, 0.15 parts of zirconium oxide, 0.7 parts of boric acid, 0.7 parts of cobalt oxide, 3.75 parts of yttrium oxide, 0.5 parts of silicon dioxide and 0.4 parts of bismuth oxide.
[0061] S1. Use a ball mill to mill the raw materials according to the ratio for 3 hours to obtain a slurry. The particle size of the slurry is 0.1-2.0 μm.
[0062] S2, the primary slurry is sieved and then prepared into a honeycomb spherical ball with a through hole in the middle by a molding machine, the ball diameter is 100 mm, the ball enters the push plate kiln for pre-sintering, the pre-sintering temperature is set to 1150 ° C, the heat preservation time is 3h, the oxygen content of the push plate kiln is 10%, and the pre-sintered material is obtained after the pre-sintering is completed;
[0063] S3, the pre-burned material after the reaction is completely screened and impurities are removed, and then crushed by a jaw crusher, and then put into a vibration mill for coarse grinding, and after coarse grinding, it is screened and put into a planetary ball mill for secondary ball milling to obtain a secondary slurry, and the particle size of the secondary slurry is 0.6-0.7μm;
[0064] S4, filtering the secondary slurry and wet pressing the slurry under a magnetic field with a magnetic field strength of 1000KA / m to obtain a green body;
[0065] S5. Sinter the green body in a push plate kiln, set the sintering temperature to 1290°C, keep the temperature for 1 hour, and perform surface treatment after cooling to obtain magnetic tiles.
[0066] Comparative Example 1
[0067] Compared with Example 1, zirconium oxide is not added to the raw materials of the magnetic tiles, and the other steps are the same as Example 1.
[0068] Comparative Example 2
[0069] Compared with Example 1, yttrium oxide is not added to the raw materials of the magnetic tiles, and the other steps are the same as Example 1.
[0070] Comparative Example 3
[0071] Compared with Example 1, zirconium oxide and yttrium oxide are not added to the raw materials of the magnetic tiles, and the other steps are the same as Example 1.
[0072] Performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 3, and the results are shown in Table 1.
[0073] The intrinsic coercive force and residual magnetic properties are tested with reference to GB / T3217-2013 Magnetic Test Methods for Permanent Magnetic (Hard Magnetic) Materials.
[0074] Flexural strength test: Use WEW-1000D hydraulic universal material testing machine to test the load limit of magnetic tiles.
[0075] Table 1
[0076] Example Intrinsic coercivity (KA / m) Remanence(mT) Flexural strength(MPa) Example 1 332.9 416.7 133.3 Example 2 341.5 423.5 152.8 Example 3 338.7 421.0 149.1 Example 4 335.1 419.1 146.0 Example 5 334.4 418.6 145.5 Comparative Example 1 312.0 405.0 108.4 Comparative Example 2 284.3 389.2 122.5 Comparative Example 3 265.0 373.0 92.6
[0077] As can be seen from Table 1, the addition ratios of zirconium oxide and yttrium oxide in Examples 1 to 3 are different, and the mechanical strength of the magnetic tiles is significantly different. The mechanical strength of the magnetic tiles in Example 2 is the best, and the synergistic effect of yttrium oxide and zirconium oxide is optimal. When one of the two raw materials is not added or neither is added, the magnetic properties and mechanical strength of the magnetic tiles in Comparative Examples 1 to Comparative Examples 3 are far inferior to those in Example 1. The magnetic tiles prepared by the present invention adjust the addition amounts of zirconium oxide and yttrium oxide in the raw materials, which can significantly improve the magnetic properties and mechanical strength of the magnetic tiles, and is beneficial to improving the service life of the magnetic tiles.
[0078] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-strength magnetic tile, characterized in that: The following raw materials are included by weight: 80-90 parts of ferric oxide, 12-15 parts of strontium carbonate, 0.4-0.6 parts of calcium carbonate, 0.1-0.2 parts of zirconium oxide, 0.5-0.7 parts of boric acid, 0.5-0.7 parts of cobalt oxide, 2-6 parts of yttrium oxide, 0.3-0.5 parts of silicon dioxide and 0.2-0.4 parts of bismuth oxide.
2. A production process for high-strength magnetic tiles as claimed in claim 1, characterized in that: The steps include: S1. Use a ball mill to mill the raw materials according to the proportion to obtain a primary slurry; S2, the primary slurry is screened and then prepared into balls by a molding machine, and the balls are pre-sintered in a push-plate kiln to obtain pre-sintered materials; S3, crushing the completely reacted pre-burned material, and then coarse grinding and fine grinding in sequence, screening and then secondary ball milling to obtain secondary slurry; S4, filtering the secondary slurry and wet pressing it to obtain a green body; S5. Sintering the green body in a push plate kiln, and performing surface treatment after cooling to obtain magnetic tiles.
3. The production process of a high-strength magnetic tile according to claim 2 is characterized in that: The ball milling time in S1 is 2-3 hours, and the particle size of the primary slurry is 0.1-2.0 μm.
4. The production process of a high-strength magnetic tile according to claim 2 is characterized in that: The material ball is a honeycomb sphere with a through hole in the middle and a diameter of 100 mm.
5. The production process of a high-strength magnetic tile according to claim 2 is characterized in that: The pre-sintering temperature in S2 is 1150-1280° C., and the pre-sintering heat preservation time is 2-3 hours.
6. The production process of a high-strength magnetic tile according to claim 2 is characterized in that: The oxygen content in the push plate kiln in S2 is 9-10%.
7. The production process of a high-strength magnetic tile according to claim 2, characterized in that: The pre-burned material in S3 is crushed by a jaw crusher, the crushed pre-burned material is coarsely ground by a vibration mill, and the coarsely ground pre-burned material is finely ground by a planetary ball mill.
8. The production process of a high-strength magnetic tile according to claim 2, characterized in that: The particle size of the secondary slurry is 0.6-0.7 μm.
9. The production process of a high-strength magnetic tile according to claim 2, characterized in that: The magnetic field of the wet pressing molding is 800-1000KA / m.
10. The production process of a high-strength magnetic tile according to claim 2, characterized in that: The sintering temperature is 1260-1290° C., and the sintering heat preservation time is 1-2 hours.
Citation Information
Patent Citations
Low-radial shrinkage ratio permanent magnetic ferrite magnet and preparation method thereof
CN104692786A
Permanent magnetic ferrite material and preparation method thereof
CN109133896A
High-structural-strength permanent magnetic ferrite magnetic shoe and preparation method thereof
CN112679206A
Preparation method of ferrite material
CN114038674A
Method of manufacturing ferrite sintered magnet
JP2002353021A